Mechanical response of HEMA gel under cyclic deformation: Viscoplasticity and swelling-induced recovery. (1st January 2015) - Drozdov, A.D.; Sanporean, C.-G.; de C. Christiansen, J.
Abstract: Observations are reported on poly(2-hydroxyethyl methacrylate) (HEMA) gels with various degrees of swelling in uniaxial tensile tests, relaxation tests, cyclic tests with a strain-controlled program, and multiple-step tests where cyclic deformation is alternated with periods of re-swelling. Constitutive equations are derived for solvent transport and the viscoplastic response of a hydrogel under an arbitrary deformation with finite strains. Adjustable parameters in the stress-strain relations are found by fitting the experimental data. Special attention is focused on the self-recovery phenomenon: a decay in plastic deformation under swelling of a preloaded sample.